Konsep al-Ḍarūrah Tentang Vaksin Astrazeneca Perspektif Majelis Ulama Indonesia - Jamaluddin Jamaluddin; Kasjim Salenda; Abdul Wahid Haddade (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to comprehensively describe the general overview of al-ḍarūrah and the AstraZeneca vaccine, examine the analysis of fiqh principles regarding al-ḍarūrah in the use of the AstraZeneca vaccine by the MUI, and analyze the MUI fatwa Number 14 of 2021 concerning the Law on the Use of the Covid-19 Vaccine Product. AstraZeneca. This study uses a qualitative-descriptive research method with library research techniques. The results showed that al-ḍarūrah is a condition that threatens human life or part of its body. Al-ḍarūrah referred to in the use of the AstraZeneca vaccine is that there is an urgent need condition (al-ḥājah al-syar'iyyah) that occupies the condition of al-ḍarūrah. This is in line with the fiqh rule